MERANGSANG MOTORIK KASAR ANAK TUNA RUNGUKELAS DASAR SEKOLAH LUAR BIASA MELALUI PERMAINAN - B. Suhartini (Jurnal Pendidikan Jasmani Indonesia, 2011)
Abstract.Deaf are individuals who have barriers to hearing both permanent and non permanent. Classification of hearing impairment based on the level of hearing loss include: Hearing loss is very mild (27-40dB), mild hearing loss (41-55dB), hearing disorders moderate (56-70dB), severe hearing loss (71-90dB), extreme hearing loss / deafness (above 91dB). Because the characteristics and constraints of being owned, deaf children require special education services forms tailored to their abilities and potential, how to communicate using sign language. Individuals with hearing impairment tend to difficulties in understanding the concept of something abstract. Even with these limitations, children with hearing disability are also entitled to a proper instruction for the development and growth can run well, especially the development of motion or psikomotornya, namely through the study of physical education. Of course, the learning process for deaf children who are different from normal children. One motor Perkambangan psychomotor aspects that must be developed by deaf children in both the base class of gross motor aspects. Gross motor movement involving the large muscles in the body, such as walking, running, jumping, jumping and so forth. Gross motor skills in young children with hearing impairment will develop more leverage if supported by a process of the correct motion. Through physical education, one way to stimulate gross motor deaf children carried out with black green game. Of course the game for deaf children is slightly different from normal children game movement. Games on deaf children adapted to the conditions of the five senses are still functioning. Games to stimulate motor deaf children carried out with black green games that use sound, such as flags or other signs, and modified by using a cue cues that can be captured through the senses of sight, and with a clear and simple rules.Keywords: Gross Motor, Deaf, Black-Green GameAbstrakTunarungu adalah individu yang memiliki hambatan dalam pendengaran baik permanen maupun tidak permanen. Individu tunarungu cenderung kesulitan dalam memahami konsep dari sesuatu yang abstrak. Meskipun dengan keterbatasan tersebut, anak penyandang tuna rungu juga berhak mendapatkan pengajaran yang layak agar perkembangan dan pertumbuhannya dapat berjalan dengan baik, terutama perkembangan gerak atau psikomotornya. Salah satu aspek psikomotor yang harus berkembang dengan baik pada tuna rungu anak kelas dasar yaitu aspek motorik kasar. Motorik kasar adalah gerak yang melibatkan otot-otot besar pada tubuh, seperti berjalan, lari, lompat, loncat dan sebagainya. Motorik kasar pada anak anak tunarungu akan berkembang lebih maksimal jika ditunjang dengan proses gerak yang benar. Salah satu cara merangsang motorik kasar anak tuna rungu dilakukan dengan permainan hijau hitam. Tentu saja permainan untuk anak tuna rungu sedikit berbeda dari permainan gerak anak normal. Permainan pada anak tuna rungu disesuaikan dengan kondisi panca indera yang masih dapat berfungsi. Permainan untuk merangsang motorik anak tuna rungu dilakukan dengan permainan hijau hitam yang menggunakan suara, misalnya bendera atau tanda yang lain, dan dimodifikasi dengan aba-aba menggunakan isyarat-isyarat yang dapat ditangkap melalui indera penglihatan, dan dengan peraturan yang jelas dan sederhana.Kata kunci: motorik kasar, tuna rungu, permainan hitam hijau.